Relevansi Pemikiran Yusuf Qardhawi dalam Konstruksi Kebijakan Pengentasan Kemiskinan di Indonesia : Sebuah Tinjauan Filantropi Islam - Anggi Prayitno; Dea Puspitasari (JKEN: Jurnal Kajian Ekonomi Nasional, 2026)
Poverty remains a major issue in Indonesia. Various government efforts to meet the basic needs of the community have not yet been optimally implemented to create long-term economic self-reliance, such as the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), Integrated Prosperous Housing Assistance (RST), Social Granaries, Remote Indigenous Communities (KAT), and Social Rehabilitation Assistance (ATENSI). This study aims to analyze the government’s efforts in poverty alleviation through the perspective of Yusuf Qardhawi, particularly regarding the optimization of zakat as an instrument of economic empowerment based on the maqashid of Sharia. This study employs a qualitative approach using the library research method. The data utilized are secondary data, consisting of books, journals, official government reports, and previous study findings. Data analysis was conducted descriptively through data reduction. The results indicate that the low effectiveness of poverty alleviation through social assistance and zakat is influenced by suboptimal zakat management, a lack of Islamic financial literacy, and a predominantly consumptive distribution of zakat. The government requires a more comprehensive approach by integrating social assistance (government) with Islamic economic instruments, namely zakat. Keywords: Poverty alleviation, Zakat, Economic empowerment